2012
DOI: 10.1177/000313481207800531
|View full text |Cite
|
Sign up to set email alerts
|

Manometric Evaluation of Internal Anal Sphincter after Fissurectomy and Anoplasty for Chronic Anal Fissure: A Prospective Study

Abstract: Chronic anal fissure (CAF) is a common painful clinical disease and its pathogenesis remains poorly understood. After failure of pharmacological therapy, that is the first-line treatment, surgical sphincterotomy remains the treatment of choice although it is followed by a high rate of anal incontinence resulting from the sphincter damage; therefore, the research of a sphincter-saving surgical option has become an important goal. The aim of this study was to evaluate the manometric modifications and the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…We recorded a low rate of recurrence (6.7%); we observed only 3 “de novo” case of post-operatory anal incontinence, which were temporary and of slight entity; patients who were already suffering experienced a temporary worsening. Moreover, MRP values started significantly reducing from 12 months [ 10 ] after the procedure to reach, at 60 months after surgery, values which were similar to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We recorded a low rate of recurrence (6.7%); we observed only 3 “de novo” case of post-operatory anal incontinence, which were temporary and of slight entity; patients who were already suffering experienced a temporary worsening. Moreover, MRP values started significantly reducing from 12 months [ 10 ] after the procedure to reach, at 60 months after surgery, values which were similar to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative manometric evaluation was performed after a reasonable period of suspension of all medical therapy influencing IAS tone. The manometric evaluation was carried out by a manometric sensor using the station pull-through as described in our previous work [11]. A manometric evaluation has been undertaken at 12 and 24 months after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Data collected on healthy subjects by our anorectal pathophysiological laboratory showed that normal values of maximum resting pressure (MRP) and maximum squeeze pressure (MSP) were respectively 68.1 ± 12.3 mmHg and 112 ± 36.2 mmHg [11]. The normal range of MRP, according to Jones et al [12], were 45-85 mmHg; so that CAF without hypertonic IAS were defined as those with MRP values < 85 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Sphincter-saving procedures have been recently reconsidered as a valuable alternative to reduce the risk of FI in both children and adults[ 6 ]. Among the latter, fissurectomy and anoplasty with a V-Y advancement flap have been employed by our team for a few years, with outstanding results[ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%